Oxygen-bridged iron-silicon diatomic electrocatalyst and preparation method and application thereof

By synthesizing the oxygen bridge and iron silicon dual -atomic electron catalyst on the oxide graphene carrier, the problem of difficulty regulating the structure of the dual -atomic catalysts is solved, and the high activity and stability under acidic and alkaline conditions are achieved. Platinum base catalyst.

CN119340410AActive Publication Date: 2025-01-21XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411738326.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-21
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The coordination structure of the diatomic catalyst is difficult to regulate, resulting in insufficient activity and stability in the tetra-electron oxygen reduction reaction, and it is unable to effectively replace the platinum-based catalyst.

Method used

The nitrate and sodium silicate are used as iron and silicon sources. Through the water thermal and chemical gas deposition technology, the oxygen bridge is combined on the oxidation graphene carrier to synthesize the iron silicon dual -atomic electrode catalyst to regulate the setting structure of the active site.

Benefits of technology

The prepared oxygen -silicon dual -atomic electron catalysts show an excellent tetra electron oxygen rear electro -catalytic performance under acidic and alkaline conditions, with high activity, strong selectivity, excellent stability, far exceeding the commercial PT/C catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005162010620000011
    Figure HDA0005162010620000011
  • Figure HDA0005162010620000012
    Figure HDA0005162010620000012
  • Figure HDA0005162010620000013
    Figure HDA0005162010620000013
Patent Text Reader

Abstract

The invention relates to a preparation method of an oxygen-bridged iron-silicon diatomic electrocatalyst, which comprises the following steps: stirring and complexing an iron source and a silicon source, mixing the complexing solution with a graphene oxide solution, and carrying out ultrasonic treatment to obtain a precursor solution; performing hydrothermal reaction on the precursor solution to obtain a reaction product; and carrying out freeze drying treatment on the reaction product, and then carrying out high-temperature nitridation by adopting a chemical vapor deposition method to obtain the oxygen-bridged iron-silicon diatomic electrocatalyst. The oxygen-bridged iron-silicon diatomic electrocatalyst prepared by the invention has excellent four-electron oxygen reduction electrocatalytic performance under acidic and alkaline conditions, and is high in activity, strong in selectivity and stable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical catalysis, and particularly relates to an oxygen-bridged iron-silicon diatomic electrocatalyst and a preparation method and application thereof. Background Art

[0002] Four-electron cathodic oxygen reduction reaction (4e - )ORR is commonly used in proton exchange membrane fuel cells (PEMFC), anion exchange membrane fuel cells (AEMFC) and zinc-air batteries (ZABs). However, due to the slow kinetics of ORR and the need for expensive platinum group metals as catalysts, this has greatly hindered the application of various types of hydrogen energy batteries.

[0003] Therefore, the development of non-precious metal catalysts with high activity, high stability and high durability has become one of the primary goals of all parties. Currently, single-atom (SAC) or diatomic catalysts (DACs) with metal-nitrogen-carbon (MNC, M=Fe, Co, Cu, Mn, Ni, etc.) coordination structures with large atomic utilization and special coordination environment are used. Although Fe-NC catalysts have high ORR performance, the active sites are easily deactivated due to Fenton reaction, which seriously affects the activity and stability of the catalyst. Therefore, it is necessary to design more efficient and stable catalysts to replace platinum-based catalysts.

[0004] Studies have shown that adjusting the coordination structure of the active site is one of the methods to optimize the ORR catalytic performance. Adding additional dopants near the active site of the MNC catalyst can reduce the electron delocalization around the catalytic center and improve the interaction with oxygen, thereby reducing the ORR reaction energy barrier. Therefore, developing a simple and effective synthesis method to regulate the coordination environment of the active site of transition metal single atom or diatomic catalysts is one of the important methods for the development of non-precious metal catalysts. Summary of the invention

[0005] The purpose of the present invention is to provide an oxygen-bridged iron-silicon diatomic electrocatalyst and its preparation method and application, which can solve the technical problem that the coordination structure of the diatomic catalyst is difficult to control;

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0008] S1. After the ferric nitrate solution and the sodium silicate solution are stirred for complexation, the complex solution is mixed with the graphene oxide solution by an ultrasonic disperser to obtain a precursor solution; the precursor solution is subjected to a hydrothermal reaction to obtain a black columnar reaction product, wherein the stirring time is 20-40 min and the ultrasonic time is 15-40 min;

[0009] S2. The reaction product is freeze-dried and then subjected to high-temperature nitridation by chemical vapor deposition to obtain an oxygen-bridged iron-silicon diatomic electrocatalyst.

[0010] Preferably, the percentage of iron in the ferric nitrate to the mass of graphene oxide in the graphene oxide solution is 1-20%; the percentage of silicon in the sodium silicate to the mass of graphene oxide in the graphene oxide solution is 1-7%, wherein the ferric nitrate solution is dissolved by anhydrous ethanol and the sodium silicate solution is dissolved by deionized water.

[0011] Preferably, the preparation method of the graphene oxide solution is: dispersing the graphene oxide solid in deionized water, ultrasonicating for 4-6 hours to obtain the graphene oxide solution; the concentration of the graphene oxide solution is 1-4 mg mL -1 .

[0012] Preferably, in step S1, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 10-15 h.

[0013] Preferably, in step S2, the freeze-drying treatment time is 3-15 hours.

[0014] Preferably, in step S2, the high-temperature nitridation using chemical vapor deposition method includes the following steps: nitridation is carried out in a mixed atmosphere of argon and ammonia, the reaction temperature is 700-900°C, the reaction time is 1-3h, the argon flow rate is 100±10sccm, and the ammonia flow rate is 50±10sccm.

[0015] Another aspect of the present invention provides an oxygen-bridged iron-silicon diatomic electrocatalyst prepared by the above-mentioned preparation method.

[0016] Another aspect of the present invention provides the use of the oxygen-bridged iron-silicon diatomic electrocatalyst as a catalyst for generating water by a four-electron oxygen reduction reaction.

[0017] Another aspect of the present invention provides the use of the oxygen-bridged iron-silicon diatomic electrocatalyst as a cathode catalyst for a zinc-air battery.

[0018] The present invention uses ferric nitrate (Fe(NO3)3) as an iron source, sodium silicate (NaSiO3) as a silicon source, and ammonia (NH3) as a nitrogen source, and adopts a hydrothermal method and chemical vapor deposition technology (CVD) to synthesize an oxygen-bridged iron-silicon diatomic electrocatalyst.

[0019] The present invention uses graphene as a carrier, and evenly complexes iron ions and silicate ions by stirring to form a positively charged complex structure. During the hydrothermal process, the iron-silicon complex is embedded in the defective parts of deprotonated graphene oxide, and then the coordination structure of the active site is regulated by chemical vapor deposition (CVD) technology to synthesize a low-cost, specially coordinated oxygen-bridged iron-silicon diatomic electrocatalyst. During the synthesis process, since graphene oxide has more defects than graphene, it can provide a large number of sites for anchoring iron atoms, and can inhibit the generation of metal clusters or nanometals, thereby forming a diatomic catalyst with rich active sites and excellent stability. In addition, during the stirring process, the iron ions and silicate ions form a stable precursor through complexation, and with the hydrothermal and high-temperature nitridation processes, the iron element and the silicon element are completely anchored on the graphene surface, thereby forming an oxygen-bridged iron-silicon diatomic structure.

[0020] The invention has simple synthesis, short preparation time, cheap precursor and abundant reserves; the oxygen-bridged iron-silicon diatomic electrocatalyst can be obtained through simple hydrothermal and chemical vapor deposition.

[0021] The oxygen-bridged iron-silicon diatomic electrocatalyst prepared by the present invention has excellent four-electron oxygen reduction electrocatalytic performance under acidic and alkaline conditions, with high activity, strong selectivity, stable performance, and far exceeds the commercial Pt / C catalyst under alkaline conditions, and is close to the commercial Pt / C catalyst under acidic conditions; and when the catalyst is used as a cathode catalyst in a zinc-air battery, it exhibits superior power density and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD pattern of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1;

[0023] Figure 2 This is a Raman spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1;

[0024] Figure 3 This is an infrared spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1;

[0025] Figure 4 This is the XRD pattern of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 4;

[0026] Figure 5 This is a Raman spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 5;

[0027] Figure 6 This is the infrared spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 5;

[0028] Figure 7TEM image of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1, where: a-200nm, b-2nm;

[0029] Figure 8 Schematic diagram of the element content of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1;

[0030] Fig. 9 The XPS fine structure peaks of N1s and Fe2p of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1, where: aN 1s, b-Fe 2p;

[0031] Fig.10 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 was heated to 4e - ORR performance, where: a-polarization curve, b-number of transferred electrons and H2O2 selectivity;

[0032] Fig.11 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 was heated to 4e - ORR performance, where: a-Tafel slope plot, b-stability curve;

[0033] Fig.12 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 was heated to 4e - ORR performance, where: a-polarization curve, b-number of transferred electrons and H2O2 selectivity;

[0034] Fig.13 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 was heated to 4e - ORR performance, where: a-Tafel slope plot, b-stability curve;

[0035] Fig.14 The discharge polarization curve and power density diagram of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 in a zinc-air battery device. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0037] The graphene oxide in the following examples is prepared by the improved Hummers method, and the specific process is as follows: a three-necked flask is placed in a water pot filled with cold water, 3g of graphite powder and a mixed solution of concentrated H2SO4 and H3PO4 (volume ratio 9:1) are added thereto, and 18g of KMnO4 is slowly added at a rotation speed of 200-350rpm.

[0038] The mixture was stirred in a water bath at 50°C for 12 h at a stirring speed of 200-350 rpm. After the solution temperature dropped to room temperature, it was poured into 400 mL of pre-frozen deionized water and stirred evenly. H2O2 was slowly added in small amounts several times under stirring until the solution turned bright yellow. The mixture was washed repeatedly with 30% by mass HCl solution, deionized water, anhydrous ethanol and ether in sequence. A light yellow graphene oxide solid was obtained after vacuum drying at room temperature for 24 h.

[0039] Example 1

[0040] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0041] 0.16 g of graphene oxide solid was added to 80 mL of deionized water, and a light brown graphene oxide solution was obtained after ultrasonic dispersion for 6 hours. At the same time, 7 mL of ferric nitrate nonahydrate solution and 1.45 mL of sodium silicate solution were mixed and stirred for 30 minutes, and then added to the graphene oxide solution, wherein the mass of iron and silicon elements accounted for 7% and 5% of the mass of graphene oxide, respectively. After ultrasonication for 15 minutes, a uniformly dispersed precursor solution was obtained.

[0042] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 180°C and the reaction time was 12h.

[0043] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2 hours. An oxygen-bridged iron-silicon diatomic electrocatalyst (FeSiNC-5.0) was obtained.

[0044] Example 2

[0045] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0046] 0.16 g of graphene oxide solid was added to 80 mL of deionized water, and a light brown graphene oxide solution was obtained after ultrasonic dispersion for 6 hours. At the same time, 7 mL of ferric nitrate nonahydrate solution and 0.87 mL of sodium silicate solution were mixed and stirred for 30 minutes, and then added to the graphene oxide solution, wherein the mass of iron and silicon elements accounted for 7% and 3% of the mass of graphene oxide, respectively. After ultrasonication for 15 minutes, a uniformly dispersed precursor solution was obtained.

[0047] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 180°C and the reaction time was 12h.

[0048] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2 hours. An iron-silicon diatomic electrocatalyst (FeSiNC-3.0) was obtained.

[0049] Example 3

[0050] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0051] 0.16 g of graphene oxide solid was added to 80 mL of deionized water, and a light brown graphene oxide solution was obtained after ultrasonic dispersion for 6 hours. At the same time, 7 mL of ferric nitrate nonahydrate solution and 0.29 mL of sodium silicate solution were mixed and stirred for 30 minutes, and then added to the graphene oxide solution, wherein the mass of iron and silicon elements accounted for 7% and 1% of the mass of graphene oxide, respectively. After ultrasonication for 15 minutes, a uniformly dispersed precursor solution was obtained.

[0052] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 180°C and the reaction time was 12h.

[0053] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2 hours. An iron-silicon diatomic electrocatalyst (FeSiNC-1.0) was obtained.

[0054] Example 4

[0055] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0056] Take 0.16g of graphene oxide solid and add it to 80mL of deionized water. After ultrasonic dispersion for 6h, a light brown graphene oxide solution is obtained. At the same time, take 20mL of ferric nitrate nonahydrate solution and 1.45mL of sodium silicate solution, mix and stir for 30min, and then add them to the graphene oxide solution, wherein the mass of iron and silicon elements account for 20% and 5% of the mass of graphene oxide, respectively. After ultrasonication for 15min, a uniformly dispersed precursor solution is obtained.

[0057] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 180°C and the reaction time was 12h.

[0058] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2 hours. An iron-silicon diatomic electrocatalyst (FeSiNC-5.0) was obtained.

[0059] Example 5

[0060] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0061] Take 0.16g of graphene oxide solid and add it to 80mL of deionized water. After ultrasonic dispersion for 6h, a light brown graphene oxide solution is obtained. At the same time, take 5mL of ferric nitrate nonahydrate solution and 1.45mL of sodium silicate solution, mix and stir for 30min, and then add them to the graphene oxide solution, wherein the mass of iron and silicon elements account for 5% and 5% of the mass of graphene oxide, respectively. After ultrasonication for 15min, a uniformly dispersed precursor solution is obtained.

[0062] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 180°C and the reaction time was 12h.

[0063] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2 hours. An iron-silicon diatomic electrocatalyst (FeSiNC-5.0) was obtained.

[0064] Example 6

[0065] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0066] Take 0.16g of graphene oxide solid and add it to 80mL of deionized water. After ultrasonic dispersion for 6h, a light brown graphene oxide solution is obtained. At the same time, take 1mL of ferric nitrate nonahydrate solution and 1.45mL of sodium silicate solution, mix and stir for 30min, and then add them to the graphene oxide solution. The mass of iron and silicon elements accounts for 1% and 5% of the mass of graphene oxide, respectively. After ultrasonication for 15min, a uniformly dispersed precursor solution is obtained.

[0067] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 150°C and the reaction time was 12h.

[0068] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 600°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 1 hour. An iron-silicon diatomic electrocatalyst (FeSiNC-5.0) was obtained.

[0069] Example 7

[0070] A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst comprises the following steps:

[0071] 0.16 g of graphene oxide solid was added to 80 mL of deionized water, and a light brown graphene oxide solution was obtained after ultrasonic dispersion for 6 hours. At the same time, 10 mL of ferric nitrate nonahydrate solution and 1.74 mL of sodium silicate solution were mixed and stirred for 30 minutes and then added to the graphene oxide solution, wherein the mass of iron and silicon elements accounted for 10% and 6% of the mass of graphene oxide, respectively. After ultrasonication for 15 minutes, a uniformly dispersed precursor solution was obtained.

[0072] The uniformly mixed precursor solution was transferred to the inner lining of the hydrothermal reactor, and the reaction temperature was set to 160°C and the reaction time was 12h.

[0073] The hydrothermal product was freeze-dried for 12 hours, and then the obtained black column product was placed in a tube furnace and subjected to high-temperature nitridation reaction in an atmosphere of argon and ammonia using chemical vapor deposition technology. The specific reaction parameters were: tube furnace temperature of 1000°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 1 hour. An iron-silicon diatomic electrocatalyst (FeSiNC-6.0) was obtained.

[0074] The catalyst performance evaluation and characterization of the examples are as follows:

[0075] The oxygen-bridged iron-silicon diatomic electrocatalyst was used as a catalyst material for the four-electron oxygen reduction reaction to generate water: the test instrument used a pine rotating disk electrode device (Rotating disk electrode, RDE and Rotating ring-disk electrode, RRDE; electrode model: AFE6R2) and a zinc-air battery (ZABs) to perform electrochemical tests related to four-electron oxygen reduction. The dispersion liquid formulation is as follows: 1 mg of catalyst solid was added to 100 μL of deionized water, 100 μL of anhydrous ethanol and 20 μL of Nafion solution, and then mixed and ultrasonicated for 1 hour, and 2.5 μL of the dispersion liquid was dropped on the disk electrode (disk area of ​​RDE: 0.196 cm 2 Or the disk area of ​​RRDE: 0.2376 cm 2The area of ​​the platinum ring is 0.2356 cm 2 ), after the first dispersion was dried, 2.5 μL of the dispersion was taken and dripped on the rotating disk electrode surface for the second time (the area mass loading of the electrocatalyst was 0.12 mg cm -2 (RDE) or 0.10mgcm -2 (RRDE)), and then dried naturally for 12 hours before conducting relevant experimental tests. A platinum wire electrode was used as the counter electrode, Ag / AgCl (3M potassium chloride solution as a salt bridge) as the reference electrode, and a disk electrode or ring disk electrode coated with an oxygen-bridged iron-silicon diatomic electrocatalyst as the working electrode to assemble a three-electrode system. Before the experiment, nitrogen or oxygen was introduced into the electrolyte until saturated. Different pH electrolytes (acidic electrolyte: 0.5M H2SO4; alkaline electrolyte: 0.1M KOH) were selected according to different experimental conditions. The electrochemical performance was evaluated at 100mV s -1 The cyclic voltammetry (CV) test was used to activate the catalyst for about 30 min until there was no air on the catalyst surface. In an oxygen-saturated electrolyte, different speeds (225-2025 rpm) were set and the voltage range was 0.2-1.1 V at 5 mV s -1 Enter the scan rate to perform linear voltammetry (LSV).

[0076] Zinc-air battery assembly and testing: Cathode electrode: Take 5 mg of homemade catalyst and 5 mg of carbon black powder, add 50 μL of isopropanol, 25 μL of polytetrafluoroethylene solution (PTFE) and 0.95 mL of deionized water, and ultrasonicate for 3-5 hours to disperse evenly. The obtained dispersion is drop-coated on 2.5*2.5 cm hydrophilic carbon paper with a drop-coating area of ​​1*1 cm and a loading of 1.0 mg cm -2 ; Anode electrode: Grind the surface of the zinc plate clean, and use anhydrous ethanol and acetone to ultrasonically clean it for 30 minutes. Electrolyte: A mixed solution of 6M KOH and 0.2M ZnCl2.

[0077] Under acidic conditions: the half-wave potential can reach 0.66V and the current density is 5.07mAcm -2 , with good stability and low H2O2 selectivity, demonstrating good 4e - ORR performance.

[0078] Under alkaline conditions: the half-wave potential can reach 0.84 V and the current density is 6.11 mA cm -2 , with good stability and extremely low H2O2 selectivity, demonstrating good 4e - ORR performance.

[0079] Figure 1Shown is the XRD pattern of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1. There are only two diffraction peaks in the figure, located at about 25° and 44°, representing the (002) and (001) planes of graphitic carbon, respectively. There are no diffraction peaks of other metals and their compounds, which indicates that iron is anchored on graphene in the form of single atoms or clusters.

[0080] Figure 2 The Raman spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown. The D peak (1350 cm -1 around) is stronger than the G peak (1580cm -1 The intensity ratio of the D peak to the G peak (ID / IG) reached 1.145, which indicates that the prepared oxygen-bridged iron-silicon diatomic electrocatalyst is defect-enriched.

[0081] Figure 3 The infrared spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown. From the figure, it can be seen that the oxygen-bridged iron-silicon diatomic electrocatalyst has abundant oxygen functional groups.

[0082] Figure 4 Shown is the XRD pattern of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 4, in which not only the (002) and (100) crystal planes of graphene are observed, but also obvious diffraction peaks of elemental iron and iron carbide are observed, which proves that excess iron is not completely anchored on the surface by graphene, and may exist in the form of elemental iron and iron carbide.

[0083] Figure 5 The Raman spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 5 is shown. The intensity ratio of the D peak to the G peak (ID / IG) reaches 1.107, which indicates that the prepared oxygen-bridged iron-silicon diatomic electrocatalyst is defect-enriched.

[0084] Figure 6 The infrared spectrum of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 6 is shown, which also illustrates that the catalyst has abundant oxygen-containing functional groups, but because of the low reaction temperature and short reaction time, the degree of nitridation is low.

[0085] Figure 7 a and 7b are low-magnification and high-magnification TEM images of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1, respectively, which show that there are abundant wrinkles on the surface of the prepared oxygen-bridged iron-silicon diatomic electrocatalyst, which is conducive to exposing more reaction active sites and facilitating the electrochemical reaction.

[0086] Figure 8Shown is a schematic diagram of the element content of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1, wherein Fe: 0.3, Si: 0.6, C: 78.4, N: 5.8, O: 14.9, which indicates that both iron and silicon elements are successfully doped into graphene.

[0087] Fig. 9 The XPS graph of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown, wherein Fig. 9 In the N1s spectrum of a, the characteristic peaks at 398.2, 399.4, 400.2, and 401.2 eV are respectively attributed to pyridinic nitrogen, iron nitrogen, pyrrolic nitrogen and graphitic nitrogen components; among them, pyridinic nitrogen and iron nitrogen components are favorable for 4e – ORR reaction proceeds. Fig. 9 b Fe 2p fine spectrum, Fe 2+ The characteristic XPS peaks of the catalyst are located at 710.3-722.1 eV. 2+ The characteristic peak shifts 1.2 eV toward the low binding energy direction, which may be due to the formation of more Fe-O-Si structures. 2+ Gain electrons from O atoms.

[0088] Fig.10 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown in the acidic 4e - ORR performance. Fig.10 a and Fig.10 b are polarization curves in 0.5 M H2SO4 electrolyte, where the catalyst has a high half-wave potential (E 1 / 2 , 0.64V) and limiting current density (J D , 5.08 mA cm -2 ); the electron transfer number (n) is 3.78 and the H2O2 selectivity is 10-15%, which both indicate that the catalyst is an ideal four-electron transfer pathway under acidic conditions.

[0089] Fig.11 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown in the acidic 4e - ORR performance, where Fig.11 a and Fig.11 b are the Tafel slope diagram and stability curve in 0.5M H2SO4 electrolyte. The calculated Tafel slope is 128mV dec -1 , indicating that the catalyst has excellent kinetic properties, and the catalyst can maintain high stability in continuous operation for up to 10 hours, and the current density does not decay significantly (91%). In summary, the oxygen-bridged iron-silicon diatomic electrocatalyst has excellent 4e- ORR activity and stability.

[0090] Fig.12 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown in alkaline 4e - ORR performance, where Fig.12 a and Fig.12 b are polarization curves in 0.1 M KOH electrolyte, where the catalyst has a high half-wave potential (E 1 / 2 , 0.85V) and limiting current density (J D , 6.05 mA cm -2 ); the electron transfer number (n) is 3.92 and the H2O2 selectivity is 1-5%, which both indicate that the catalyst is an ideal four-electron transfer pathway under alkaline conditions.

[0091] Fig.13 The oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 is shown in alkaline 4e - ORR performance, where Fig.13 a and Fig.13 b are the Tafel slope diagram and stability curve in 0.1M KOH electrolyte, and the calculated Tafel slope is 115mV dec -1 , indicating that the catalyst has excellent kinetic properties, and the catalyst can maintain high stability in continuous operation for up to 10 hours, and the current density does not decay significantly (90%). In summary, the oxygen-bridged iron-silicon diatomic electrocatalyst has excellent 4e - ORR activity and stability.

[0092] Fig.14 The figure shows the discharge polarization curve and power density of the oxygen-bridged iron-silicon diatomic electrocatalyst prepared in Example 1 in a zinc-air battery device, which can reach 80 mW cm -2 Peak power density, with superior power density and stability.

Claims

1. A method for preparing an oxygen-bridged iron-silicon diatomic electrocatalyst, characterized in that: The following steps are involved: S1, after the iron source and the silicon source are stirred for complexation, the complexation solution is mixed with the graphene oxide solution by ultrasonication to obtain a precursor solution; subjecting the precursor solution to a hydrothermal reaction to obtain a reaction product; S2. The reaction product is freeze-dried and then subjected to high-temperature nitridation by chemical vapor deposition to obtain an oxygen-bridged iron-silicon diatomic electrocatalyst.

2. The preparation method according to claim 1, characterized in that: The percentage of iron in the iron source to the mass of graphene oxide in the graphene oxide solution is 1-20%; the percentage of silicon in the silicon source to the mass of graphene oxide in the graphene oxide solution is 1-7%.

3. The preparation method according to claim 1 or 2, characterized in that: The iron source is ferric nitrate; the silicon source is sodium silicate.

4. The preparation method according to claim 1, characterized in that: In step S1, the preparation method of the graphene oxide solution is: dispersing the graphene oxide solid in deionized water, ultrasonicating for 4-6 hours, to obtain a graphene oxide solution; the concentration of the graphene oxide solution is 1-4 mg mL -1 .

5. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 160-200°C, and the time of the hydrothermal reaction is 10-15h;.

6. The preparation method according to claim 1, characterized in that: In step S2, the freeze-drying treatment time is 3-15 hours.

7. The preparation method according to claim 1, characterized in that: In step S2, the high-temperature nitridation using chemical vapor deposition method includes the following steps: nitridation is carried out in a mixed atmosphere of argon and ammonia, the reaction temperature is 700-900°C, the reaction time is 1-3h, the argon flow rate is 100±10sccm, and the ammonia flow rate is 50±10sccm.

8. An oxygen-bridged iron-silicon diatomic electrocatalyst prepared by the preparation method according to any one of claims 1 to 8.

9. Use of the oxygen-bridged iron-silicon diatomic electrocatalyst according to claim 8 as a catalyst for generating water by a four-electron oxygen reduction reaction.

10. Use of the oxygen-bridged iron-silicon diatomic electrocatalyst according to claim 8 as a cathode catalyst for a zinc-air battery.

Citation Information

Patent Citations

  • Iron nitride / nitrogen-doped graphene aerogel as well as preparation method and application thereof

    CN103721736A

  • Nitrogen-doped graphene-supported iron-based nanoparticle composite catalyst and preparation method thereof

    CN105289687A

  • High-performance ternary Fe-Co-Ni co-doped nitrogen-containing carbon material as well as preparation method and application thereof

    CN108336374A

  • Ni-Fe diatomic electrocatalyst, and preparation method and application thereof

    CN111185176A

  • Silicon-doped iron-nitrogen / carbon composite catalyst as well as preparation method and application thereof

    CN111864219A

Cited By

  • Oxygen-linked monatomic-oxide transition metal catalyst as well as preparation method and application thereof

    CN120119286A